PENINGKATAN CYBER RELATIONS MELALUI INSTAGRAM SEBAGAI BAKAL PERSONAL BRANDING SISWA SMAN 7 BEKASI - Ghaniyyu Widiyaningrum, Alifiah (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
In the era of rapid digitalization, social media, especially Instagram, has become the main platform for self-expression and social interaction, especially among teenagers and high school students. This phenomenon opens up opportunities for students to build self-image or personal branding. Students of SMA Negeri 7 Bekasi, as part of the digital generation, are highly exposed to social media, including Instagram, which is an important tool in forming and managing their personal branding. This personal branding not only reflects the image in the real world, but also includes their ability to manage their image in cyberspace. The importance of personal branding on Instagram is increasingly relevant for students of SMA Negeri 7 Bekasi, because it can affect their journey after graduation, such as scholarship selection, university admission, or the world of work. Having a positive personal branding in cyberspace is a significant added value. This community service program will be implemented with systematic training and evaluation methods to ensure that the objectives are achieved. This training aims to provide students with an understanding of the concept of personal branding and how to implement it on Instagram. It is hoped that students can recognize their potential, develop digital skills, and use Instagram to build strong and positive personal branding. This program aims to increase students' awareness of the importance of self-image in cyberspace and provide practical strategies to manage their digital reputation effectively.